Relationship between Physical Activity and Cardiorespiratory Health in Urban Children - Arna, Yessy Dessy (PT. Anagata Sembagi Education, 2025)
Lifestyle changes that occur due to urbanization and modernization have a significant impact on the physical activity of children in urban areas. Children in urban areas tend to spend more time with sedentary activities such as playing gadgets or watching TV, which contributes to a decrease in physical activity. This condition potentially increases the risk of obesity, cardiorespiratory disorders, and other health problems. The lack of open spaces and adequate sports facilities exacerbates this situation. Decreased physical activity in children is closely linked to a reduced quality of life, including their cognitive and motor abilities. Studies show that regular physical activity can improve lung capacity and heart function, thereby reducing the risk of cardiorespiratory disorders. Therefore, it is important to integrate more active physical activities in children's daily lives through programs that provide easy access to sports facilities and adequate open spaces. This effort is expected to improve the quality of life of urban children and maintain their optimal cardiorespiratory health